2015
DOI: 10.1089/scd.2014.0230
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitor of Glycogen Synthase Kinase 3β 6-Bromoindirubin-3-oxime Inhibits Hematopoietic Regeneration in Stem Cell Recipient Mice

Abstract: Small-molecule inhibitors of glycogen synthase kinase 3β (GSK3β) have demonstrated strong anti-leukemia effects in preclinical studies. Here, we investigated the effect of GSK3β inhibitor 6-Bromoindirubin-3-oxime (BIO) previously shown to inhibit leukemia cell growth in vitro and of animal models on hematopoietic regeneration in recipients of stem cell transplant. BIO administered to immunocompromised mice transplanted with human hematopoietic stem cells inhibited human stem cell engraftment in the bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The proliferation of human mesenchymal stem cells have been reported to increase 4 fold when treated with 6-BIO [83]. Contrastingly, 6-BIO has also been reported to delay CD34 + cell expansion [84]. The apoptotic role of 6-BIO, BIOacetoxime in cancer has been vastly exploited in human melanoma cells, human leukemia cells, human ovarian cancer cells, human neuroblastoma cells [58,[85][86][87].…”
Section: -Bio (6-bromoindirubin-3′-oxime)mentioning
confidence: 99%
“…The proliferation of human mesenchymal stem cells have been reported to increase 4 fold when treated with 6-BIO [83]. Contrastingly, 6-BIO has also been reported to delay CD34 + cell expansion [84]. The apoptotic role of 6-BIO, BIOacetoxime in cancer has been vastly exploited in human melanoma cells, human leukemia cells, human ovarian cancer cells, human neuroblastoma cells [58,[85][86][87].…”
Section: -Bio (6-bromoindirubin-3′-oxime)mentioning
confidence: 99%
“…Currently, 6BIO has been tested in certain preclinical disease models, such as in Parkinson disease models, intracerebral hemorrhage models, and leukemia models, and such research has provided promising evidence of efficacy (Shen et al., 2015; Suresh et al., 2017; Zhao et al., 2017). Our study also points to the clinical potential of therapeutic 6BIO in liver.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some matters still require attention before being applied to a clinical setting. A recent study indicated that GSK-3β inhibitor suppresses B- and T-cell development in stem cells, which signifies it should be tested carefully, particularly in conjunction with stem cell transplantation and adoptive T-cell immunotherapy (Shen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the anti-inflammatory activity of some oximes has been reported to be comparable to standard anti-inflammatory drugs, such as indomethacin, diclofenac, and dexamethasone [ 18 , 19 , 20 ]. On the other hand, the introduction of an oxime group into an appropriate chemical backbone is a reasonable approach for the preparation of cytotoxic agents, and many oxime derivatives have been reported to have therapeutic activity for cancer [ 2 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and neurodegenerative disorders [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%